(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In any project whether IT or non-IT based, communication plays an important role. Communication in an IT project would be dealing with among others communication between the project management office (PMO) and the stakeholders and also communication among the team members of the project. According to Project Management Institute (PMI) report on 2017, inadequate/poor communication contributes 30% of the project‘s failure. Working on a project with diverse members‘ background and limited experiences would be challenging, especially the window for the project time frame is not that big. This paper presents a case study of IT project development and highlights the experience of a PMO strategizing to improve communication among team members to bridge the gap between them. Both conventional and unconventional methods were applied for the team to achieve their project goals especially when working on the project during the Covid-19 pandemic. At the end of the paper some reflections of how the effective communication processes contributed to a higher chance of project success are shared.